High-Risk HPV Genotype Distribution According to Cervical Cytology and Age. (3rd November 2022) - Trama, Jason P; Trikannad, Charulata; Yang, Jing Jing; Adelson, Martin E; Mordechai, Eli
Abstract: Background: A retrospective study of a single laboratory's results from patients in the United States to investigate high-risk human papillomavirus (HPV) genotype distribution according to cervical cytology and age was performed. Methods: Anonymous results of 23 580 patients' cervical specimens sent to Medical Diagnostic Laboratories, LLC, for cervical cytology and HPV testing between August 2020 and August 2021 were analyzed. Results: Overall, any of the 14 high-risk HPV genotypes identified were detected in 2302 of the 23 580 patients (9.8%), with HPV 52 (1.4%), HPV 39 (1.3%), HPV 51 (1.3%), and HPV 16 (1.2%) being the most frequent in all patients. Multiple high-risk HPV infection was observed in 1.3% of all patients. HPV 16 was most likely to be a single high-risk genotype detected as compared with detection with other high-risk HPV genotypes, in contrast to HPV 33, which is least likely to be a single high-risk genotype detected as compared with detection with other high-risk HPV genotypes. High-risk HPV detection was greatest in patients under 25 years old (<21-year-olds, 24.6%, and 21–25-year-olds, 25.4%). In patients with low-grade squamous intraepithelial lesions, the most frequently detected high-risk HPV genotypes were HPV 51 (10.5%) and HPV 39 (9.1%), and in patients with high-grade squamous intraepithelial lesions, the most frequently detected high-risk HPV genotypes were HPV 16 (25.6%) and HPV 52 (17.1%). Conclusions: HPV genotyping and cervical cytology data analysis may contribute to and inform cervical cancer screening and HPV vaccination programs.